2020
DOI: 10.31351/vol29iss1pp247-252
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Preliminary Biological Activity Evaluation of New N- Substituted Phthalimide Derivatives

Abstract: A A new series of bases of Schiff (H2-H4) derived from phthalic anhydrideweresynthesized. These Schiff bases were prepared by the reaction of different amines (tyrosine methyl ester, phenylalanine methyl ester, and isoniazid) with the phthalimide derived aldehyde with the aid of glacial acetic acid or triethylamine ascatalysts. All the synthesized compounds were characterized by (FT-IR and 1HNMR) analyses and were in vitro evaluated for their antimicrobial activity against six various kinds of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…4-(1,3-dioxoisoindolin-2-yl) benzoic acid 7 Phthalic anhydride and 4-aminobenzoic acid were reacted in an equimolar ratio of 1 mmoL each in 15 ml of glacial acetic acid.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…4-(1,3-dioxoisoindolin-2-yl) benzoic acid 7 Phthalic anhydride and 4-aminobenzoic acid were reacted in an equimolar ratio of 1 mmoL each in 15 ml of glacial acetic acid.…”
Section: Methodsmentioning
confidence: 99%
“…6 Phthalimide derivatives are given a biological activity via the imide ring and structural core (-CO-N(R)-CO-). 7 Several pharmacophore subunits, including pyrazoles and diazoles, (oxo and thioxo) triazoles, benzo-(oxazoles, imidazoles, and thiazoles), and compounds containing the azomethine group (Schiff bases), were added using the molecular hybridization method to boost the biological action of phthalimide derivatives. 8 The most commonly used types of organic substances include Schiff bases -with the imine (-C=N-) - [14]; they are very helpful for creating several bioactive medicinal molecules from primary amine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both phthalimide and Nsubstituted phthalimide possessed biological efficiency such as anti-inflammatory [1,2], analgesic, anti-depressant [3,4], antioxidant [5], antimicrobial agent [5][6][7], and other activates [8][9][10][11][12]. The important applications of phthalimide due to the structural properties that are possessed like a hydrophobic aryl ring, the group of electron-donor, and hydrophobic 5-membered ring help to improve the biological activity of Phthalimide [13]. The study [14] has shown that, the possibility of using phthalimide and its derivatives in the biological field and used as an anti-bacterial.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2,3 ] There has been an increasing interest in synthesizing new cyclic imide derivatives as prospective antimicrobial agents in recent years, as the structure is a promising scaffold. [ 2,4–6 ]…”
Section: Introductionmentioning
confidence: 99%